2020
DOI: 10.37190/abb-01652-2020-02
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gait speed on plantar pressure variables in individuals with normal foot posture and flatfoot

Abstract: Purpose: It is not known how gait speed affects plantar pressure characteristics in flatfoot. The aim of this work was to investigate the effects of gait speed on plantar pressure variables in flatfoot by comparing it to normal foot posture. Methods: Thirty individuals with flatfoot and 30 individuals with normal foot posture were recruited. Plantar pressure variables were obtained by a pressure-sensitive mat at self-selected slow, normal, and fast speeds. All assessments were performed on the dominant foot, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The current study also found that, with the increase in gait speed, the peak pressure of each area of the sole had a corresponding increase, except for the MF area. Changes in these areas were consistent with the results of previous study, the plantar pressure distribution of sarapus was affected by gait speed, and the analysis of plantar pressure was different under asynchronous speed [33]. However, during the walking process of the individual with flexible flatfoot in the experiment wearing different insoles, the peak pressure in the MF area was relatively stable at slow, normal, and fast gait speed.…”
Section: Discussionsupporting
confidence: 90%
“…The current study also found that, with the increase in gait speed, the peak pressure of each area of the sole had a corresponding increase, except for the MF area. Changes in these areas were consistent with the results of previous study, the plantar pressure distribution of sarapus was affected by gait speed, and the analysis of plantar pressure was different under asynchronous speed [33]. However, during the walking process of the individual with flexible flatfoot in the experiment wearing different insoles, the peak pressure in the MF area was relatively stable at slow, normal, and fast gait speed.…”
Section: Discussionsupporting
confidence: 90%
“…Plantar impulse represents the cumulative effect of force over a given time period while walking. Typically, as gait speed increases, the peak plantar pressure and force in different regions of the foot also increase 24 . However, due to the the shortening of the stance phase with higher gait speed, the plantar impulse may behave differently.…”
Section: Discussionmentioning
confidence: 99%